THE STUDENT'S PERCEPTION OF ONLINE LEARNING AT UNIVERSITAS SULTAN AGENG TIRTAYASA - Eri Rahmawati; Kamil, Insan; Syafrizal (Aisyah Journal of English Language Teaching (AIJELT), 2023)
This research aims to investigate students’ perception on online learning as learning method at 8th semester of English Education Department in Universitas Sultan Ageng Tirtayasa based on their perception. The researcher used qualitative research with thematic analysis as study method. Open Questionnaire and interview were used as the data collecting technique. Subjects of this research were the 8th semester English Education Department Universitas Sultan Ageng Tirtayasa, which consists of 40 students. Based on the findings, it is found out that the students have mainly negative perception towards online learning as learning method, and there are some problem in conducting it. The students believe it affects their ability to focus, concentrate, and absorb the learning material. Next, the students also feel online learning giving them mental and emotional effect, because the lack of social interaction affected the way they learn and the way they absorb the knowledge from the lecturer.